All-ukrainian research and design institute of analytical instrumentation “Ukranalyt” celebrates its 45th anniversary - Dashkovsky, A. A.; Mikhejeva, I. L. (Technology and design in electronic equipment, 2014)
The paper describes the history of creation and progress of the institute as a scientific organization. The information is presented on areas of scientific and technical activity, and the results obtained by the stuff during 45-years history of the enterprise.